THE ANALYSIS REVENUE OF PREMIUM MELON FRUIT FARMERS AT PUSAT PENGUMPULAN HASIL TANAMAN KEKAL PENGELUARAN MAKANAN PERADONG MALAYSIA - Rahmat Suryanto Pirngadi; Farhan Aditya Sagala (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Malaysia is a country located on the equator that has a tropical climate with a high level of soil fertility that makes it possible to increase production in the agricultural sector. Where agriculture is the most substantial field in contributing to the gross domestic product of Malaysia. Peradong Food Produce Collection Center is an agricultural institution managed by the Department of Agriculture of the State of Malaysia located in Peradong. Peradong is one of the Districts in Kuala Terengganu, Terengganu Province, Malaysia. This institution focuses on increasing innovation in agriculture, especially peremium melon plants by establishing 16 greenhouses for melon plant cultivation with 4 assisted farmers. The research location was carried out at the Peradong Food Expenditure Perennial Crops Collection Center with the sampling technique carried out by the census method. The analysis model used in solving this problem is using income analysis with the equation ???? = ???????? - ????????. From the results of the analysis, it was found that the net income earned by assisted farmers from the cultivation of premium melon farming at the Peradong Food Expenditure Perishable Crops Collection Center was RM 16,058 / MT / farmer.